2020
DOI: 10.1515/zpch-2019-1599
|View full text |Cite
|
Sign up to set email alerts
|

ZnO, CuO and Fe2O3 green synthesis for the adsorptive removal of direct golden yellow dye adsorption: kinetics, equilibrium and thermodynamics studies

Abstract: In the present investigation, ZnO, CuO and Fe2O3 were prepared via green route and utilized for the sequestration of DGY (Direct Golden Yellow) dye. Affecting variables i.e., temperature, contact time, adsorbent dose and pH were optimized for maximum sequestration of dye from aqueous medium. The pH 2, adsorbent dose 0.1 g/50 mL dye solution, temperature 30 °C and 50 mg/L dye initial concentration were best levels for efficient dye adsorption and equilibrium was attained in 30 min reaction time. The dye sequest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Moreover, the study of Praipipat et al found that the chicken and duck eggshell beads modified with iron­(III) oxide-hydroxide also presented higher RB4 dye removal than the addition of zinc oxide into the same raw materials . In addition, other studies also reported that the addition of iron oxide or magnetite (Fe 3 O 4 ) in carboxymethyl cellulose helped in the increase of the dye removal efficiency. , Furthermore, the study of Noreen et al also supported that the addition of Fe 2 O 3 into the extracted Cassia Fistula gave a higher direct golden yellow removal than ZnO and CuO . Therefore, LBF was a potential adsorbent material for dye removal and could be used as an alternative adsorbent for wastewater treatment in the future.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study of Praipipat et al found that the chicken and duck eggshell beads modified with iron­(III) oxide-hydroxide also presented higher RB4 dye removal than the addition of zinc oxide into the same raw materials . In addition, other studies also reported that the addition of iron oxide or magnetite (Fe 3 O 4 ) in carboxymethyl cellulose helped in the increase of the dye removal efficiency. , Furthermore, the study of Noreen et al also supported that the addition of Fe 2 O 3 into the extracted Cassia Fistula gave a higher direct golden yellow removal than ZnO and CuO . Therefore, LBF was a potential adsorbent material for dye removal and could be used as an alternative adsorbent for wastewater treatment in the future.…”
Section: Results and Discussionmentioning
confidence: 99%
“…25,26 Furthermore, the study of Noreen et al also supported that the addition of Fe 2 O 3 into the extracted Cassia Fistula gave a higher direct golden yellow removal than ZnO and CuO. 27 Therefore, LBF was a potential adsorbent material for dye removal and could be used as an alternative adsorbent for wastewater treatment in the future.…”
Section: Effect Of Concentrationmentioning
confidence: 99%
“…The rationale behind this reduction in the adsorption efficiency is that the rise in temperature usually weakens the adsorptive forces present among the dye molecules and the active locations present on the adsorbent exterior which ultimately reduces the efficiency of adsorption (Salleh, Mahmoud, Karim and Idris, 2011). Noreen et al (2020) studied the temperature's influence over the efficiency of adsorption of various dyes by employing the oxides of Mg, Zn and Fe. It was examined that with the temperature increment to 40 °C, the optimum adsorption was deduced as 40.94 mg g -1 for oxides of Mg, 46.25 mg g -1 for oxides of Zn and 42.86 mg g -1 for oxides of Fe.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…At lower temperatures, the rigorous movement in the molecules of dye resulted in an increase in the effectiveness of adsorption. While, at higher temperatures, the decline in the efficiency of adsorption got reported because of the damaging/inactivity of active binding sites over the adsorbent exterior surface (Noreen, et al, 2020).…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…ZnO nanoparticles are important host material for La ions, because they are a well-known material for providing luminescence in doped particles. Therefore, co-doping ZnO with Mn and La could overcome the above-mentioned drawbacks and enhance the cell efficiency [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%